Agriculture Intelligente face au Climat (AIC) et Systeme d'information Climatique (SIC): Formation pour le Secteur Privé - Siagbe, Golli; Derenoncourt, Marie Ena; Chabot, Philippe; Jaquet, Stéphanie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
As part of the Gender-Smart Accelerator activity within the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, a two-day workshop was organized on 25-26 October 2022, in Dakar, Senegal. The workshop was aimed to reinforce the capacity of the private sector on climate change, climate-smart agriculture and climate information services. This includes: (1) Basic understanding of climate change (2) Climate-Smart Agriculture Practices (3) Climate Information Services (4) Bundling opportunities including CSA and CIS (4) Impact of Climate Risk on Business Operations, Profitability and Cash Flow (6) Gender-Smart Investing Roadmap for agricultural SME financing. Value chain actors (producers, processors, aggregators) and financial actors (banks, impact investors, insurance companies) that finance the agricultural sector participated in the workshop.